Automatic Evaluation of Landmarks for Image-Based Navigation Update. (17th May 2009) - Lang, Stefan; Kirchhof, Michael
Abstract : The successful mission of an autonomous airborne system like an unmanned aerial vehicle (UAV) strongly depends on its accurate navigation. While GPS is not always available and pose estimation based solely on Inertial Measurement Unit (IMU) drifts, image-based navigation may become a cheap and robust additional pose measurement device. For the actual navigation update a landmark-based approach is used. It is essential that the used landmarks are well chosen. Therefore we introduce an approach for evaluating landmarks in terms of the matching distance, which is the maximum misplacement in the position of the landmark that can be corrected. We validate the evaluations with our 3D reconstruction system working on data captured from a helicopter.